Avaliação do risco de reativação de tuberculose em pacientes em uso de imunobiológicos em serviços de referência em reumatologia no estado do Ceará - Evangelista, Priscila Dourado (2019)
Rheumatic diseases, rheumatoid arthritis, and spondyloarthritis are autoimmune, chronic and marginal pathologies. These diseases may be peripheral or axial joints (spinal column). When untreated, individual carriers may develop musculoskeletal sequences and, in some cases, extra-articular manifestations. Pharmacological treatment can be done with NSAIDs, synthetic and biological DMARDs, depending on the disease and indications for each stage of the disease. Biological DMARDs are represented by anti-TNF, anti-IL-6, co-stimulation modulators and anti-CD20 immunobiological agents. The use of drugs that modulate the immune system invariably results in a greater risk for the development of infections. Surgery the behavior in behavior of immunobiológicos, deserves special emphasis in the growth of tuberculosis. This is particularly the case for those using anti-TNF, with a latent reactivation of latent tuberculosis among patients. In this context, the present study evaluated the epidemiological profile of 173 patients with rheumatic diseases, observing that the female gender is the most prevalent; an average of diagnoses of rheumatic disease at the age of 52 years; the most frequent BMI is an overweight class; an average of anti-TNF use was 33.91 months, with adalimumab being the most used (52.02%). As for latent tuberculosis, the strongest protocol for the diagnosis of ILTB was a previous indicator of the case with M. tuberculosis. Of the 173 patients treated, 39 were diagnosed with ILTB, 4 of whom developed TB, 2 of whom were treated for ILTB, 1 were not treated and 1 was not informed.